2016
DOI: 10.5604/12321966.1203904
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Rheumatoid Arthritis (RA) in rural and urban areas of Poland – 2008–2012

Abstract: Objective. The aim of this study is to investigate the morbidity rate due to Rheumatoid Arthritis (RA) in the Polish population during 2008-2012, calculated per 1,000 inhabitants, and taking into account the differences between provincess, area of residence (urban or rural) and gender. Materials and method. From the NFZ IT systems, PESEL number information was obtained for all 17 types of services contracted in 2008-2012, for patients whose main diagnosis in the report was the ICD-10 disease code: M05.X-seropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
1
10
0
3
Order By: Relevance
“…In Poland, the number of RA sufferers is increasing [32]. People with rheumatoid arthritis experience stress caused by their disability and persistent pain and are dependent on other people.…”
Section: Discussionmentioning
confidence: 99%
“…In Poland, the number of RA sufferers is increasing [32]. People with rheumatoid arthritis experience stress caused by their disability and persistent pain and are dependent on other people.…”
Section: Discussionmentioning
confidence: 99%
“…The joint synovitis leads to progressive destructions in bones and cartilages, and causes significant disabilities and even permanent functional loss due to the erosion of bones surfaces if it is untreated [2]. The global prevalence of RA in adult populations is approximately 0.5% -1.0%, and it is more common in women than in men (two-to four-folds), with a most common age at onset between the fourth and sixth decade of life [3]. Pathologically, RA is mainly three steps process that begins with autoimmunity development, followed by a local inflammation and in the final step, bone destruction is induced [4].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have highlighted inadequate access to specialist healthcare services for those with rheumatic and musculoskeletal disease (RMD) living in rural and remote locations. [13][14][15][16] However, in a recent systematic review of the literature, we found very limited evidence as to whether outcomes are poorer for individuals with rheumatic disease living in rural settings. 17 No eligible studies examined work outcomes.…”
Section: Spondyloarthritismentioning
confidence: 89%